Visualità e intermedialità in Hugo von Hofmannsthal (Studia austriaca, 2014)
In Tod des Tizian (1892) the painted image and its verbal evocation carry out an important function of poetics. In this verse play, Titian’s last painting offers a new representation perspective, which to a certain extent invalidates his previous production. Hofmannsthal here deals with a theme deeply rooted in his aesthetic program. The impulse towards a form supported by a sort of reciprocal strengthening of life and art takes on an eminently ethic configuration in which the aesthetic individual rediscovers his specific duty.